Вы находитесь на странице: 1из 23
Remember from last lecture, single element (2 nodes) matrix can be written as follows u
Remember from last lecture, single element (2 nodes)
matrix can be written as follows
u 1 e
k e
u 2 e
e
e
k
e
u
e k
u
= F
1
2
1
F 1 e
1 e
2 e
F 2 e
e
e
e
Element e
-k
u
+
k
= F
1 e u
2
2
e
e
u
e u
= F
1
2
1
e
e
e
u
+
k e u
= F
1
2
2
The stiffness matrix from:
1
2
1
2
= F 1 2 1 e e e u + k e u = F 1
= F 1 2 1 e e e u + k e u = F 1
= F 1 2 1 e e e u + k e u = F 1
= F 1 2 1 e e e u + k e u = F 1
= F 1 2 1 e e e u + k e u = F 1
= F 1 2 1 e e e u + k e u = F 1

1

2

= F 1 2 1 e e e u + k e u = F 1

k

e

- k e

- k e

k

e

1 2
1
2
Lets write the individual matrix for each element 1, 2 1 Nodes 2, 3 3

Lets write the individual matrix for each element

Lets write the individual matrix for each element 1, 2 1 Nodes 2, 3 3 3,

1,

2

1

Nodes

2, 3 3 3, 4
2,
3
3
3,
4
• R 1 Node 1
R 1
Node 1

K 1 (u 2 – u 1 ) K 1 (u 2 – u 1 )

Node 2

K 2 (u 3 – u 2 ) K 2 (u 3 – u 2 )

Node 3

K 3 (u 4 – u 3 )

K 3 (u 4 – u 3 )

Node 4

K 4 (u 5 – u 4 )

K 4 (u 5 – u 4 )

Node 5

(u 5 – u 4 ) K 4 (u 5 – u 4 ) Node 5

R 1 – unknown reaction force

P

u 1 u 2 u 3 u 4 • • • • 1 k 1
u 1
u 2
u 3
u 4
1
k
1
2
k 2
3
k 3
4
k 4
5
P – applied load

ele. 1

4 4, 5  k e k e  Element 1 1 1  
4
4, 5
k
e
k
e
Element 1
1
1
k
e
e
k
1
1
This is a plain
matrix
1
2
3
4
5
0
0
0
0
0
1
0
0
0
0
0
2
0
0
0
0
0
3
0
0
0
0
0
4
0
0
0
0
0
5

ele. 2

ele. 3

ele. 4

 k e k e  Element 1 1 1   k e k
k
e
k
e
Element 1
1
1
k
e
k
e
1
1

Element 1 is elated to nodes 1 & 2 So we can place this matrix in the plain global matrix at the intersection of nodes 1 & 2

0

 

1

2

0

0

0

0

0

0

 

0

0

0

0

0

0

3

0

0

0

0

0

4

0

0

0

0

0

5

0

0

0

0

0

R 1 – unknown reaction force

      R 1 – unknown reaction force • • R 1
• • R 1 K 1 (u 2 – u 1 ) K 1 (u
R
1
K 1 (u 2 – u 1 )
K 1 (u 2 – u 1 )

Node 1

Node 2

K 2 (u 3 – u 2 ) K 2 (u 3 – u 2 )

Node 3

K 3 (u 4 – u 3 )

u 1 u 2 u 3 u 4 • • • 1 k 1 2
u 1
u 2
u 3
u 4
1
k 1
2
k 2
3
k 3
4
k 4
5
P – applied load

ele. 1

ele. 2

ele. 3

ele. 4

3

4

0

0

0

0

0

0

0

0

0

0

5

0

0

0

0

0

1

2

  K 3 (u 4 – u 3 )

3

  Node 4

4

  K 4 (u 5 – u 4 )

5

K 4 (u 5 – u 4 )

Node 5

P

1

2

3

4

5

u 1 u 2 u 3 u 4 • • • • • R 1
u 1
u 2
u 3
u 4
R
1
R 1 – unknown
reaction force
k
e
k
e
Element 2
Node 1
2
2
1
K 1 (u 2 – u 1 )
K 1 (u 2 – u 1 )
ele. 1
k 1
k
e
k
e
2
2
2
Node 2
Element 2 is elated to nodes 2 & 3
So we can place this matrix in the
plain global matrix at the
intersection of nodes 2 & 3
K 2 (u 3 – u 2 )
K 2 (u 3 – u 2 )
ele. 2
k 2
Node 3
3
1
2
3
4
5
K 3 (u 4 – u 3 )
 0
0
0
0
0 
1
ele. 3
k 3
0
0
0
 2
  K 3 (u 4 – u 3 )
0
0
0
3
0
0
0
0
0
 Node 4
4
4
0
0
0
0
0
5
  K 4 (u 5 – u 4 )
k 4
ele. 4
K 4 (u 5 – u 4 )
1
2
3
4
5
Node 5
0
0 
5
1
P
P – applied load
0
0
2
0
0 0
 3
0
0
0
0
0
 4
0
0
0
0
0
  5
 k e k e  3 3    k e k e
 k e k e  3 3    k e k e
k
e
k
e
3
3
k
e
k
e
3
3

Element 3

Element 3 is elated to nodes 3 & 4 So we can place this matrix in the plain global matrix at the intersection of nodes 3 & 4



 

1

2

0

0 0

0 0

0

0

0

0

0

4         1 2 0 0 0 0 0
3 4 0 0 0 0 0 0 0 0 0 0
3
4
0
0
0
0
0
0
0
0
0
0

5

0

0

0

0

0



1

2

0

0 0

0 0

3 4 5 0 0 0  1  0 0 2  k e
3
4
5
0
0
0
1
0
0
2
k
e
k
e
3
3
0
3
k
e
k
e
0
4
3
3
0
0
0
5

1

2

3

4

5

u 1 u 2 u 3 u 4 • • • • • R 1
u 1
u 2
u 3
u 4
R
1
R 1 – unknown
reaction force
Node 1
1
K 1 (u 2 – u 1 )
K 1 (u 2 – u 1 )
ele. 1
k 1
2
Node 2
K 2 (u 3 – u 2 )
K 2 (u 3 – u 2 )
ele. 2
k 2
Node 3
3
K 3 (u 4 – u 3 )
ele. 3
k 3
K 3 (u 4 – u 3 )
Node 4
4
K 4 (u 5 – u 4 )
k 4
ele. 4
K 4 (u 5 – u 4 )
Node 5
5
P
P – applied load
 k e k e  4 4    k e k e
 k e k e  4 4    k e k e
k
e
k
e
4
4
k
e
k
e
4
4

Element 4

4    k e k e  4 4   Element 4 Element
Element 4 is elated to nodes 4 & 5 So we can place this matrix
Element 4 is elated to nodes 4 & 5
So we can place this matrix in the
plain global matrix at the
intersection of nodes 4 & 5
1
2
3
4
5
0
0
0
0
0
1
0
0
0
0
2
 0
 0
0
0
0
0
3
0
0
0
0
4
 0
0
0
0
0
  0
5
1
2
3
4
5
0
0
0
1
0
0
2
0
0
3
k
e
k
e
0 0
4
4
4
0 0
0
k
e
k
e
5
4
4
u 1 u 2 u 3 u 4 • • • • • R 1
u 1
u 2
u 3
u 4
R
1
R 1 – unknown
reaction force
Node 1
1
K 1 (u 2 – u 1 )
K 1 (u 2 – u 1 )
ele. 1
k 1
2
Node 2
K 2 (u 3 – u 2 )
K 2 (u 3 – u 2 )
ele. 2
k 2
Node 3
3
K 3 (u 4 – u 3 )
ele. 3
k 3
K 3 (u 4 – u 3 )
Node 4
4
K 4 (u 5 – u 4 )
k 4
ele. 4
K 4 (u 5 – u 4 )
Node 5
5
P
P – applied load
The final global matrix of the system is obtained simply by assembling or adding the
The final global matrix of the system is obtained simply by
assembling or adding the individual element matrices
1
2
3
4
5
The overlapping
k
e
k
e
1
1
0
0
0 
1
k
e
k k
e
e
k
e
0
0
2
1
1
“K” will be added
in the system
global matrix
2
2
k
e
0
k
e
k
e
k
e
0
3
2
2
3
3
0
0
e e
k
e
k k
k
e
4
3
3 4
4
0
0
0
e
e
k
k
5
4
4
The assembly of the above matrix gives the global matrix of the system
 k
k
0
0
0
1
1
k
k
k
k
0
0
1
1
+
2
2
0
k
k
k
k
0
2
2
+
3
3
0
0
k
k
k
k
This method gives
the same matrix
which we have
developed from
individual equilibrium
3
3
+
4
4
0
0
0
k
k
4
4
equation for each
node

To calculate the stiffness of any element

c b b wall 1 a A 2 B a C 3 D a 4
c
b
b wall
1
a
A
2
B
a
C
3
D
a
4
F

k = stiffness

E = Modules of elasticity

A = cross sectional area ( width x thickness )

l = length of the element

Example 1 For the suspended plate which is fixed to the roof as shown in
Example 1 For the suspended plate which is fixed to the roof as shown in

Example 1

Example 1 For the suspended plate which is fixed to the roof as shown in Fig.
Example 1 For the suspended plate which is fixed to the roof as shown in Fig.
Example 1 For the suspended plate which is fixed to the roof as shown in Fig.

For the suspended plate which is fixed to the roof as shown in Fig. below

a. Model the plate in suitable FE form.

b. Calculate the stiffness of each element, k e

c. Write the element – nodes table.

d. Set the global stiffness matrix of the model.

e. Solve for the elongation in each element

E = Modulus of Elasticity = 100 GPa All dimensions in mm t = thickness
E = Modulus of Elasticity = 100 GPa
All dimensions in mm
t = thickness of the plate = 1mm
a = 20 mm
a a a a a 100 200
a
a
a
a
a
100
200

10 kN

Example 1

Element(e) Nodes 1 1, 2 2 1, 2 3 1, 2 4 2, 3
Element(e)
Nodes
1
1,
2
2
1,
2
3
1,
2
4
2,
3
a a a a a 100 Element 1 200
a
a
a
a
a
100
Element 1
200
1, 2 3 1, 2 4 2, 3 a a a a a 100 Element 1
1
1
1
1
2 3 1, 2 4 2, 3 a a a a a 100 Element 1 200

Element 2

a a a a 100 Element 1 200 1 E l e m e n t

Element 3

a 100 Element 1 200 1 E l e m e n t 2 Element 3
a 100 Element 1 200 1 E l e m e n t 2 Element 3

2

Element 4

3

10kN

200 1 E l e m e n t 2 Element 3 2 Element 4 3

Model the plate in suitable FE form.

10 kN

k = stiffness E = Modules of elasticity A = cross sectional area ( width x thickness ) l = length of the element

To calculate the stiffness

) l = length of the element To calculate the stiffness Since elements 1, 2, &
) l = length of the element To calculate the stiffness Since elements 1, 2, &
) l = length of the element To calculate the stiffness Since elements 1, 2, &

Since elements 1, 2, & 3 have the same area. Module of elasticity & length, hence their stiffness are equal K 1 = K 2 = K 3

length, hence their stiffness are equal K 1 = K 2 = K 3 E =
E = 100 GPa t = thickness of the plate = 1mm a = 20
E = 100 GPa
t = thickness of the plate = 1mm
a = 20 mm

Individual matrix of each element

Element 1

k

1

e

k

1

e

k

1

e

k

1

1

0

2

0

0 0

0 0

k k

2

1

e e

k

3

k k

e

2 1

k

e

0

e

e

3

Element 2

Element 3

Element(e)

Nodes

 

 

3

0

0

0

k

2

e

k

2

1

2

3

e

k

2

k

2

e

e

 

  

k

3

e

k

3

e

Element 4

k

e

4

k

4

e

k

4

k

4

e

e

e

k

2

e

k

1

e

k

2

1

k

e

e

k

e

k

3

e

k

3

e

4

k

e

4

0

k

e

4

k

e

4

k

3

k

3

e

e

1 1,

2 1,

3 1,

4 2,

2

2

2

3

 k 3 k 3 e e     1 1, 2 1, 3

k

+

1

k

1

k

+

2

k

2

0

k

3

k

3

k

1

k

+

1

k

2

k

2

+

k

3

k

4

k

3

+

k

4

0

k

4

k

4

k k 3 1 k k + k 3 1 2
k
k
3
1
k
k
+
k
3
1
2

k

2

+

k

2

0

k 3 + k 3 4
k
3
+
k
3
4

k

2

+

k

k

4

k

4

k

4

k 3 1 2 k 2 + k 2 0 k 3 + k 3 4

k

0

+

1

k

1

4 k 4  k     0      +
4 k 4  k     0      +
4 k 4  k     0      +
4 k 4  k     0      +

Substitute the above k values into the developed global matrix gives

K

G

= 10

7

6

0

6

6

11

5

0

5

5

Remember from last lecture G ] = G [K {u } {F } Zero because
Remember from last lecture
G
]
=
G
[K
{u
}
{F
}
Zero because its a fixed point
So we can write the matrix as
6
6
0
  u 
1
0
7
10
6
11
5
u
=
0
2
0
5
5
u
10000
 
3
In any matrix if there zero then the column
and row of the zero will be cancelled
6
6
0
  u 
0
1
7
10
6
11
5
u
=
0
2 
0
5
5
u
10000
 
3 
U 1 =0 because it’s a fixed poin
11
5   u 
0
7
2
10
=
5
5
u
10000
 
3

10

7

 11 5   u   0  2 =   
 11
5   u 
0
2
=
 5
5
u
10000
 
3
  5 5 u 10000    3    We get from
  5 5 u 10000    3    We get from

We get from this matrix two equations

Multiplying the matrices (refer to matrix lecture slides) gives

the matrices (refer to matrix lecture slides) gives Two equations with two unknowns can be easily

Two equations with two unknowns can be easily solved and get

U

U

U

2

3

1

=0.167mm

=0.367mm

=0

Example 2: The beam shown in the figure below is cantilevered at one end and
Example 2: The beam shown in the figure below is cantilevered at one end and
Example 2: The beam shown in the figure below is cantilevered at one end and
Example 2: The beam shown in the figure below is cantilevered at one end and
Example 2: The beam shown in the figure below is cantilevered at one end and

Example 2:

The beam shown in the figure below is cantilevered at one end and is pulled by a force of 100 N at the other end. Calculate the total elongation of the beam.

h

=

0.0425m

1 h = 0.0275 m 2 E1 h2 E2 h 1 0.1m 0.1m
1
h
= 0.0275 m
2
E1
h2
E2
h 1
0.1m
0.1m
the total elongation of the beam. h = 0.0425m 1 h = 0.0275 m 2 E1

100 N

E= 200000 Pa

38

Ex 2: Solution
Ex 2: Solution

Use 2 uniform cross section elements.

Ex 2: Solution Use 2 uniform cross section elements. h = 0.0425m 1 h = 0.0275
h = 0.0425m 1 h = 0.0275 m 2 E1 E2 h2 h 1 39
h
= 0.0425m
1
h
=
0.0275 m
2
E1
E2
h2
h 1
39
Ex 2: Solution Use 2 uniform cross section elements. h = 0.0425m 1 h = 0.0275

100 N

Ex 2: Solution Use 2 uniform cross section elements. h = 0.0425m 1 h = 0.0275
Two Elements Stiffness Matrix R E1 E2 100 N 100 N 1 k 1 k
Two Elements Stiffness Matrix R E1 E2 100 N 100 N 1 k 1 k
Two Elements Stiffness Matrix R E1 E2 100 N 100 N 1 k 1 k
Two Elements Stiffness Matrix R E1 E2 100 N 100 N 1 k 1 k

Two Elements Stiffness Matrix

R

E1 E2 100 N 100 N 1 k 1 k 2
E1
E2
100 N
100 N
1
k
1
k 2

Node 1

Node 2

Node 3

Two Elements Stiffness Matrix R E1 E2 100 N 100 N 1 k 1 k 2
By using the method to assemble the global matrix from individual elements matrix. The resulted
By using the method to assemble the global matrix from individual elements matrix. The resulted
By using the method to assemble the global matrix from individual elements matrix. The resulted

By using the method to assemble the global matrix from individual elements matrix. The resulted global stiffness matrix for the system is:

to assemble the global matrix from individual elements matrix. The resulted global stiffness matrix for the

K=

to assemble the global matrix from individual elements matrix. The resulted global stiffness matrix for the
to assemble the global matrix from individual elements matrix. The resulted global stiffness matrix for the
Ex 2: Solution Since this is a uniaxial 1-D problem, the elements can be simplified
Ex 2: Solution Since this is a uniaxial 1-D problem, the elements can be simplified
Ex 2: Solution Since this is a uniaxial 1-D problem, the elements can be simplified

Ex 2: Solution

Ex 2: Solution Since this is a uniaxial 1-D problem, the elements can be simplified as
Ex 2: Solution Since this is a uniaxial 1-D problem, the elements can be simplified as

Since this is a uniaxial 1-D problem, the elements can be simplified as 2 springs in series.

R 1 k 1 k 2 Node 1 Node 2 Node 3 h = 0.0425
R
1
k
1
k 2
Node 1
Node 2
Node 3
h
= 0.0425 m
h
= 0.0275 m
E1
E2
100 N

100 N

with element stiffness, k i = E * A i / L Where A i =2h (cross section area is square)

k 1 = [(200000*0.0425 2 )/0.1] = 3612.5 N/m k 2 = [(200000*0.0275 2 )/0.1] = 1512.5 N/m

42

Ex 1: Solution
Ex 1: Solution

Global Stiffness Matrix**:

K=

Ex 1: Solution Global Stiffness Matrix**: K= = 43

=

43

Ex 1: Solution Global Stiffness Matrix**: K= = 43
Ex 1: Solution Global Stiffness Matrix**: K= = 43
Ex 1: Solution Global Stiffness Matrix**: K= = 43
Ex 1: Solution Global Stiffness Matrix**: K= = 43
Ex 2: Solution Arranging the problem in matrix form (K*x = F) yield; = A

Ex 2: Solution
Ex 2: Solution
Ex 2: Solution Arranging the problem in matrix form (K*x = F) yield; = A known

Arranging the problem in matrix form (K*x = F) yield;

Arranging the problem in matrix form (K*x = F) yield; = A known solution, u1 =
=
=

A known solution, u1 = 0. Thus the problem can be reduced to (by eliminating first column & first row):

= A known solution, u1 = 0. Thus the problem can be reduced to (by eliminating
= A known solution, u1 = 0. Thus the problem can be reduced to (by eliminating

44

=

= A known solution, u1 = 0. Thus the problem can be reduced to (by eliminating
Ex 1: Solution -1 Option 1 solution : Using the inverse matrix method, x =
Ex 1: Solution
Ex 1: Solution
Ex 1: Solution -1 Option 1 solution : Using the inverse matrix method, x = K

-1

Option 1 solution: Using the inverse matrix method, x = K

* F ;

-1 Option 1 solution : Using the inverse matrix method, x = K * F ;
-1 =
-1
=
-1 Option 1 solution : Using the inverse matrix method, x = K * F ;

=

-1 Option 1 solution : Using the inverse matrix method, x = K * F ;

=

-1 Option 1 solution : Using the inverse matrix method, x = K * F ;

Refer to previous matrix lecture slides

45

Option 2 solution : Use two equations solution = Two equations with two unknowns can
Option 2 solution : Use two equations solution = Two equations with two unknowns can
Option 2 solution : Use two equations solution = Two equations with two unknowns can

Option 2 solution: Use two equations solution

Option 2 solution : Use two equations solution = Two equations with two unknowns can be

=

Option 2 solution : Use two equations solution = Two equations with two unknowns can be
Option 2 solution : Use two equations solution = Two equations with two unknowns can be

Two equations with two unknowns can be easily solved and get

U

U

U

2

3

1

=0.027

=0.093

=0

: Use two equations solution = Two equations with two unknowns can be easily solved and